Effect of acute moderate-intensity cycling on cfDNA levels considering menstrual cycle phases - Sawai, Akemi; Shida, Takashi; Hoshikawa, Yoshihiro; Hatanaka, Sho; Ueda, Mashiro; Kato, Yuri; Tokinoya, Katsuyuki; Natsui, Hiroaki; Kawakami, Yasushi; Takekoshi, Kazuhiro (Frontiers in Sports and Active Living, 2024)
We aimed to determine the effects of exercise on cell-free DNA (cfDNA) levels and concentration changes during the menstrual cycle in participants with regular menstrual cycles and no exercise habits. Eleven sedentary female students with regular menstrual cycles and ovulation performed bicycle exercises at 60% VO2max for 30 min during the menstrual, ovulatory, and luteal phases. Blood samples were collected before (Pre), immediately after (Post 0), 30 min after (Post 30), and 60 min after (Post 60) exercise. Blood concentrations of ovarian hormones, cfDNA, prostaglandin F2a (PGF2α), interleukin-6 (IL-6), and aromatase were evaluated. Based on the concentration of ovarian hormones, seven individuals were finally analyzed. No significant phase difference was observed in cfDNA across all time points. cfDNA and aromatase concentrations significantly increased from Pre to Post 0 in all phases. Serum estradiol (E2) levels were significantly higher in the luteal phase at all time points than in the menstrual phase; however, serum progesterone (P4) levels were significantly higher in the luteal phase at all time points than in the menstrual and ovulatory phases. E2 levels significantly increased from Pre to Post 0 in the ovulatory and luteal phases, whereas P4 levels increased in the luteal phase. Progesterone to estradiol level ratio (P4/E2) changes from Pre to Post 0 (%baseline) during the luteal phase were significantly negatively correlated (r =-0.82, p=0.046) with the changes in cfDNA from Pre to Post 0. Furthermore, the repeated measures correlation between P4/E2 and cfDNA level showed a significant negative correlation in ovulatory and luteal phases. The results indicate that while resting cfDNA levels are unlikely to be affected by a woman's menstrual cycle, the increase in cfDNA after exercise is higher in the ovulatory phase (when only E2 increases) and lower in the luteal phase (when E2 and P4 increase with exercise) compared to that in the menstrual phase (when E2 and P4 are in low levels), suggesting the contribution of increased ovarian hormone levels after exercise.